FEM and multi-objective optimization of steel case hardening. (January 2015) - Cavaliere, P.; Perrone, A.; Silvello, A.
Highlights: The paper shows the development of a model based on very broad experimental activity. The data were employed to provide a provisional tool for case hardened steel behavior. A very good experimental–numerical correlation was found. Optimization of the process was performed to maximize superficial and bulk hardness. Abstract: Steel case hardening is a thermo-chemical process largely employed in the machine components production mainly to solve wear and fatigue damage in materials. The process is strongly influenced by many different variables such as material properties and processing parameters. In the present study, the influence of such parameters affecting the carburizing quality and efficiency was evaluated. The aim was to streamline the process by numerical–experimental analysis allowing for the definition of optimal conditions for the success of the process. The optimization software used is modeFRONTIER ® (Esteco); a set of input parameters was defined (steel composition, carbon potential, carburizing time, etc.) and evaluated on the basis of an optimization algorithm carefully chosen for the multi-objective analysis.